Tożsamość sakramentalnego misterium w przymierzu Chrystusa z Kościołem i w małżeństwie - Rychlicki, Czesław (Ius Matrimoniale, 2017)
A close connection between anthropological and theological dimension of marriage triggers a series of problems and requirements in the key of Christian ethics. Marriage as a good gift from the Creator, granted in the divine act of creation (cf. Genesis 1, 26-27), is a natural institution raised by Christ to the dignity of a sacrament. As a result, it constitutes a research subject of both secular and theological sciences, including canon law. As a natural institution, in the Old Testament it is a symbol of the covenant of God’s love to Israel, which confirms its greatness and at the same time is a challenge to cooperate in the act of creation with God (cf. Genesis 1, 28). With time, as a privileged creation of the Creator, marriage received special attention of Jesus Christ, who developed its meaning and importance in the key of new covenant of love between Christ and Church. In the message of St. Paul, marriage not only symbolizes the covenant of God’s love to humans, but is also “a realistic renewal” of this covenant of love (cf. Ephesians 5, 31-32). Thereby, marriage created by the Creator at the beginning of history, reaches in the covenant between Christ and Church (new God’s people) its sacramental dimension as an institution “reconstructing” God’s love to humans. This unique value constitutes for a man and woman, united in marriage, a requirement of faithfulness and permanence of their covenant, modeled of the covenant of God’s love to humans. As far as the unity and indissolubility of marriage is concerned, over the centuries the Christian tradition has taken note of a number of examples of faithful obedience and drastic failure to comply with the rules of marriage. Cultural changes in our century clearly indicate drastic changes in the institution of marriage and family, not only in religious, but also natural dimension and lead to dehumanization of the human person. The destruction of marriage and family as fundamental units of society, leads to its impairment and degradation in cultural and existential aspect.